Sosialisasi Penggunaan Media Sosial Tiktok Untuk Meningkatkan Penjualan Di Kampung Akrilik Padang - Muhammad Afdhal; Radius Prawiro; Selvi Zola Fenia (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
Abstract Acrylic Village is a small business that uses TikTok as a promotional medium.Based on the pre-observations that have been carried out by the researchers, Kampung Acrylic suggests that TikTok is very helpful in promoting its products.Based on this, we are interested in conducting community service (PKM) related to Promotional Strategies by utilizing socialization on the use of Tiktok social media to increase sales.